Formulasi Sediaan Bedak Tabur dari Rimpang Kencur (Kaempferia galanga L.) sebagai Antioksidan dengan Menggunakan Metode DPPH - Fransina Metrix Heatubun; Niken Lutfiyanti; Annie Rahmatillah (Lembaga Pengembangan Kinerja Dosen, 2025)
Free radicals can damage the skin and cause premature aging, so antioxidants are needed to protect the skin. Kencur rhizome (Kaempferia galanga L.) contains compounds that have potential as natural antioxidants. This study aims to develop a formulation of loose powder preparation from kencur rhizome simplisia with concentration variations of 4%, 6%, and 8%, and evaluate its physical quality and antioxidant activity using the DPPH method. The physical quality of the powder preparation included organoleptics, homogeneity, adhesion, pH, irritation, and hedonic test. The results showed that all formulations were organoleptically stable and homogeneous and the pH of the preparation was stable at 25°C but changed significantly at 40°C ± 2°C (p<0.05). Adhesion was less than optimal (p>0.05). The irritation test showed mild reactions in some panelists for F2 and F3. Hedonic test showed that F3 was most preferred by the panelists. Antioxidant activity of kencur rhizome extract (IC50 22.65 ppm), F1 (IC50 163.14 ppm), F2 (IC50 54.16 ppm), and F3 (IC50 35.48 ppm).